Synergetic Effects of Temperature and Perpendicular Magnetic Field on Zn-Ni Alloy Electrodepositing Process - Benachour, N.; Chouchane, S.; Chopart, J.P. (Asian Journal of Chemistry, 2021)
The zinc-nickel alloys were electrodeposited on stainless steel substrates during a chloride acid bath. The electroplating processes were investigated under a moderate perpendicular magnetic flux at uncommon temperatures. The coatings obtained were characterized by scanning microscopy (SEM) including EDX and X-ray diffraction (XRD). Chronopotentiometric curves were additionally implemented for electrochemical analysis. Structural analysis revealed that the obtained alloys consisted of a mix of the homogeneous phase γ-Ni3Zn22 and α-Zn-Ni at 70 ºC. The alloys variations observed within the chemical composition, crystallographic phases and morphology of the alloys. It is often explained particularly, by the progressive hydrogen reaction and therefore the evolution of the adsorbed intermediate species. The synergetic effect was significant at 70 ºC within the 1T field, including the appearance of normal co-deposition.